Perdagangan Perempuan - Abang Ishar (PSGA LP2M IAIN Pontianak, 2017)
One of the moral decadencies within societies is woman trafficking. In the past Greek ancient, women were considered as low-rank and disgusting creatures. The conservative perspective had continued in the Europe for decades, that it was being reversed after renaissance in England and aufklarung in Germany. At that moment, women had similar position with men. Meanwhile, in the Arab world before Islam came, women had been acknowledged as poor and ashamed people that should work as men’s servant. Thus, before having converted to Islam, Umar bin Khattab had buried his own daughter alive. Furthermore, the similar facts occured in some countries included Indonesia. In Indonesia, especially, before being freed from the colonial, women had only works as servant, kitchen keeper, and could not study. Moreover, after colonialism, women have different destiny, they become more indepence and professional, even there is still an exploitation within women these days.